Penyisihan NH3 Pada Limbah Cair Domestik Dengan Rotary Alga Biofilm Reactor - Deassy Amelia; Shinta Elystia; Aryo Sasmita (Jurnal Online Mahasiswa (JOM) Bidang Teknik dan Sains, 2021)
Rotating Alga Biofilm Reactor (RABR) is a biological wastewater treatment using microorganisms with suspension and biofilm culture processes. The microorganism used in this study was the microalgae Chlorella sp. that require nutrients such as carbon, nitrogen and light for growth. This nutrient source is obtained from domestic wastewater which has a high organic matter content. In this study, variations of disc surface roughness (type 1, type 2 and type 3) were performed on the Rotary Alga Biofilm Reactor process and contact time (0, 1, 3, 5 days) to remove NH3, parameters. Reactor with variations of disk surface roughness type 3 was able to remove NH3 concentration of 3.26 mg/l and removal efficiency of 83.84% on the 5th day with a total number of microalgae cells based on suspension and biofilm of 8.65 x 106 cells/ml. Keywords: Chlorella sp., Rotary Alga Biofilm Reactor (RABR), Disc Surface Roughness, Domestic wastewater, NH3